RELEFANSI NILAI PAK DALAM UPACARA KAUS NONO MA TASAEB NONO BERDASARKAN LENSA PAUL TILICH BAGI MASYARAKAT DESA IUS MOLLO KECAMATA MOLLO UTARA - Baun, Nofriana; Djawa, Maya; Silla, Abia; Koeslulat, Welmenci (Jurnal Dedikasi Pendidikan, 2025)
This study examines the Christian Religious Education values in the Kaus Nono Ma Tasaeb Nono ceremony, analyzed through Paul Tillich's lens, within the community of Ius Mollo Village, North Mollo District. Employing qualitative methods with observation and interviews, the findings reveal that the ceremony embodies spiritual, social, and symbolic meanings: safeguarding households from calamities, honoring women as they adapt to their husband's extended family, and uniting spouses as one entity. Through Tillich's perspective, the Christian Religious Education transcends doctrinal teaching, becoming a transformative process that integrates intellectual, emotional, spiritual, and cultural dimensions, with culture acting as a unifying force in the community